Silicone Sheet Containing All‐Trans Retinoic Acid and Hydroquinone for the Treatment of Epidermal Melanosis. Issue 8 (11th April 2013) - Iida, Shoko; Takushima, Akihiko; Ohura, Norihiko; Sato, Suguru; Kurita, Masakazu; Harii, Kiyonori
<x xml:space="preserve">Abstract</x> Background Although bleaching treatment using all‐trans retinoic acid (RA) and hydroquinone (HQ) improves epidermal melanosis, the application of two medications and the irritant dermatitis induced by RA inconvenience patients. To overcome these problems, we developed a silicone sheet containing RA and HQ. Objective To compare the efficacy of a silicone sheet containing RA and HQ with that of conventional bleaching treatment. Method Silicone sheets containing 1% RA and 5% HQ were applied at night during the bleaching phase of 4 weeks, followed by application of sheets containing 5% HQ during the healing phase of 4 weeks. Hemifacial epidermal melanosis, for which the sheets were applied, was compared with a contralateral face which was treated conventionally using RA and HQ. Twenty‐four Japanese women who were enrolled in this study and followed up for more than 6 months were analyzed. Results RA/HQ sheets improved epidermal melanosis, as did the conventional bleaching method, but irritant dermatitis occurred less in patients treated using silicone sheets. Conclusion RA/HQ sheets, which are easily applied to face skin, can improve epidermal melanosis to the same extent as conventional bleaching.